The Influence of R&D Intensity on the Performance and Application of Fundamental and Relative Equity Valuation Methods – Part I - Arne Nowak; Ernst Fahling (ISM Research Journal, 2015)
This paper reviews the relevant literature on equity valuation techniques and addresses the question to what degree the vanishing information content of accounting numbers influences the precision, applicability and analysts choice of fundamental and relative valuation methods. In that context it outlines the mathematical evolution of fundamental valuation techniques and how the advancements amended the shortcomings of predecessors. It furthermore elaborates on the method, implementation and obstacles of relative equity valuation and reviews analysts preferences with regard to the application of different valuation approaches. The paper reveals that the residual earnings method is the most accurate fundamental valuation method that even outperforms the price to forward earnings multiple, which is testified to be the best per-former among relative methods. Nevertheless, from a practical perspective, the discounted cash flow model as well as the price to earnings multiple have developed into industry stand-ards that are still most widely applied among analysts.
Keywords: 650